Osteogenic peptides in periodontal ligament stem cell-containing three-dimensional bioscaffolds promote bone healing. (25th February 2022) - Cai, Mingxiang; Liu, Yaoyao; Tian, Yinping; Liang, Yan; Xu, Zinan; Liu, Fangchen; Lai, Renfa; Zhou, Zhiying; Liu, Minyi; Dai, Jian; Liu, Xiangning
Abstract : The oligopeptide SDSSD promotes the osteogenic differentiation of human periodontal ligament stem cells. The 3D bioscaffolds with SDSSD enhance bone formation and the repair effect of bone defects in mice by regulating the AKT signaling pathway. Abstract : Bone tissue engineering shows great potential in bone regeneration; however, the lack of bone growth factors with high biocompatibility and efficiency is a major concern. Oligopeptides have drawn great attention due to their high biological efficacy, low toxicity, and low molecular weight. The oligopeptide SDSSD promotes the osteogenesis of human periodontal ligament stem cells (hPDLSCs) in vitro. The SDSSD-modified three-dimensional (3D) bioscaffolds promote osteogenesis and bone formation in the subcutaneous pockets of BALB/c nude mice and facilitate bone healing in vivo . Mechanistically, SDSSD promoted bone formation by binding to G protein-coupled receptors and regulating the AKT signaling pathway. 3D-printing bioscaffolds with SDSSD may be potential bone tissue engineering materials for treating bone defects.